Atypical Porcine Pestivirus (APPV) as a New Species of Pestivirus in Pig Production - Gatto, Igor Renan Honorato; Sonálio, Karina; de Oliveira, Luís Guilherme (Frontiers in Veterinary Science, 2019)
The genus Pestivirus, which belongs to the Flaviviridae family, includes the ssRNA + viruses responsible for infectious diseases in swine, cattle, sheep, goats and other domestic and wild animals. Recently, a several putative pestiviruses species have been discovered and characterized in mammal species (giraffe pestivirus, antelope pestivirus, HoBi virus, Bungowannah virus and Linda virus), and one of them, is a genetically distinct pestivirus, named atypical porcine pestivirus (APPV) discovered using next-generation sequencing (NGS) technology. APPV has been detected in piglets with congenital tremor (CT) from four different continents, including North America, South America, Europe and Asia. There is strong evidence that experimental inoculation and in field outbreaks involving APPV induces CT in piglets. Still, the splay leg (SL) syndrome has been observed concurrently with CT, induced by APPV in experimental studies and some field cases. Animals with a persistently infection condition can shed the virus over time. Viral-RNA was frequently detected in different tissues from CT-piglets, but, central nervous tissue is the most consistently sample to detect APPV in high loads. Also, APPV genome has been recently detected in semen, preputial swabs from boar studs, wild boars and domestic adult pigs, known to be all clinically health. Phylogenetic analysis revealed that APPV sequence (complete or partial polyprotein) has a high genetic diversity between viral strains detected in different countries and formed independent clusters according to geographic location. Additional studies are needed to evaluate the molecular detection and sero-prevalence of APPV in the world. However, more research is needed to understand new clinical presentations associated with APPV infection, and the economic losses related to the virus in pig production worldwide.